Isolation and Characterization of Electrochemically Active Subsurface Delftia and Azonexus Species - Jangir, Yamini; French, Sarah; Momper, Lily M.; Moser, Duane P.; Amend, Jan P.; El-Naggar, Mohamed Y. (Frontiers in Microbiology, 2016)
Continental subsurface environments can present significant energetic challenges to the resident microorganisms. While these environments are geologically diverse, potentially allowing energy harvesting by microorganisms that catalyze redox reactions, many of the abundant electron donors and acceptors are insoluble and therefore not directly bioavailable. Extracellular electron transfer (EET) is a metabolic strategy that microorganisms can deploy to meet the challenges of interacting with redox-active surfaces. Though mechanistically characterized in a few metal-reducing bacteria, the role, extent, and diversity of EET in subsurface ecosystems remains unclear. Since this process can be mimicked on electrode surfaces, it opens the door to electrochemical techniques to enrich for and quantify the activities of environmental microorganisms in situ. Here, we report the electrochemical enrichment of microorganisms from a deep fractured-rock aquifer in Death Valley, CA, USA. In experiments performed in mesocosms containing a synthetic medium based on aquifer chemistry, four working electrodes (WEs) were poised at different redox potentials (272, 373, 472, 572 mV vs. SHE) to serve as electron acceptors, resulting in anodic currents coupled to the oxidation of acetate during enrichment. The anodes were dominated by Betaproteobacteria from the families Comamonadaceae and Rhodocyclaceae. A representative of each dominant family was subsequently isolated from electrode-associated biomass. The EET abilities of the isolated Delftia strain (designated WE1-13) and Azonexus strain (designated WE2-4) were confirmed in electrochemical reactors using WEs poised at 522 mV vs. SHE. The rise in anodic current upon inoculation was correlated with a modest increase in total protein content. Both genera have been previously observed in mixed communities of microbial fuel cell enrichments, but this is the first direct measurement of their electrochemical activity. While alternate metabolisms (e.g., nitrate reduction) by these organisms were previously known, our observations suggest that additional ‘hidden’ interactions with external electron acceptors are also possible. Electrochemical approaches are well positioned to dissect such extracellular interactions that may be prevalent in the subsurface.